Curable resin composition and cured product thereof
The curable resin composition, with polyfunctional urethane (meth)acrylate and specific monofunctional compounds, addresses mechanical and water absorption issues in stereolithography, providing improved impact and heat resistance for three-dimensional modeling.
Patent Information
- Application Number
- JP2020089618
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-21
- Filing Date
- 2020-05-22
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-05-22
AI Technical Summary
Existing photocurable resin compositions used in stereolithography do not provide sufficient mechanical strength, impact resistance, and water absorption, limiting their application in high-temperature and high-humidity environments.
A curable resin composition comprising polyfunctional urethane (meth)acrylate, hydrophilic and hydrophobic monofunctional radically polymerizable compounds, and rubber particles, with specific weight average molecular weights and content ratios, to enhance impact resistance and reduce water absorption.
The composition achieves a cured product with excellent impact resistance, heat resistance, and low water absorption, suitable for three-dimensional modeling and stereolithography applications.
Smart Images

Figure 0007608070000002 
Figure 0007608070000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a curable resin composition and a cured product thereof. [Background technology]
[0002] There is known an optical three-dimensional modeling method (hereinafter referred to as "optical modeling") in which a photocurable resin composition is selectively irradiated with light based on the three-dimensional shape of a three-dimensional model to form a cured resin layer, and then the process is repeated to produce a shaped object in which the cured resin layers are integrally laminated.
[0003] Specifically, according to slice data generated from the three-dimensional shape data of the three-dimensional model to be produced, the liquid surface of the liquid photocurable resin composition contained in the container is irradiated with light such as an ultraviolet laser, and a cured resin layer having a desired thickness and a desired pattern is formed. Next, a photocurable resin composition is supplied onto the cured resin layer, and light is irradiated in the same manner to form a new cured resin layer bonded to the previously formed cured resin layer. In this way, the cured resin layers are laminated in a pattern based on the slice data, thereby obtaining a desired three-dimensional object. According to such a photo-molding method, if there is three-dimensional shape data of the three-dimensional model, it is possible to easily produce a three-dimensional object with a complex shape.
[0004] The application of stereolithography is expanding to the creation of prototypes for shape confirmation (rapid prototyping), the creation of working models for functionality verification, and the creation of molds (rapid tooling).Furthermore, in recent years, the use of stereolithography has begun to spread to the creation of actual products (rapid manufacturing).
[0005] In view of this, there is a demand for a photocurable resin composition that can be used to mold three-dimensional objects having high impact resistance comparable to that of general-purpose engineering plastics and high heat resistance that does not deform even at relatively high temperatures. In addition to the above, there is also a demand for low water absorption that shows high dimensional stability even in a high-humidity environment.
[0006] Patent Documents 1 and 2 disclose a resin composition for optical three-dimensional modeling, which contains a urethane (meth)acrylate, an ethylenically unsaturated compound having a radical polymerizable group, rubber particles, and a radical polymerization initiator. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-51665 A [Patent Document 2] JP 2014-201688 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the cured products of the resin compositions for optical 3D modeling disclosed in Patent Documents 1 and 2 are not sufficient in terms of achieving both good mechanical strength and water absorbency. [Means for solving the problem]
[0009] The present disclosure aims to provide a curable resin composition capable of obtaining a cured product having low water absorption and excellent impact resistance and heat resistance. The curable resin composition according to the present disclosure contains a polyfunctional urethane (meth)acrylate (A) having at least two (meth)acryloyl groups and at least two urethane groups in the molecule, a hydrophilic monofunctional radically polymerizable compound (B) having one radically polymerizable functional group in the molecule, a hydrophobic monofunctional radically polymerizable compound (C) having one radically polymerizable functional group in the molecule, rubber particles (D), and a radical polymerization initiator (E); The hydrophilic monofunctional radically polymerizable compound (B) contains at least one of an acrylamide compound and an N-vinyl compound, The content of the rubber particles (D) is 8 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the total of the radical polymerizable compounds not including the (D). and , The weight average molecular weight of the polyfunctional urethane (meth)acrylate (A) is 1,000 or more and 60,000 or less, It is characterized in that: Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a curable resin composition that can form a cured product having low water absorption and excellent impact resistance and heat resistance, and is suitable for three-dimensional modeling. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing a configuration example of a photo-fabrication apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention (hereinafter also referred to as "the present embodiment") will be described. Note that the embodiment described below is merely one of the present embodiments, and the present invention is not limited to these embodiments.
[0013] <Multifunctional urethane (meth)acrylate (A)> The polyfunctional urethane (meth)acrylate (A) contained in the curable composition of this embodiment is a urethane (meth)acrylate having at least two (meth)acryloyl groups and at least two urethane groups in the molecule.
[0014] The polyfunctional urethane (meth)acrylate (A) may be, for example, a compound obtained by reacting a hydroxyl group-containing (meth)acrylate compound with a polyvalent isocyanate compound, or a compound obtained by reacting an isocyanate group-containing (meth)acrylate compound with a polyol compound. Alternatively, a compound obtained by reacting a hydroxyl group-containing (meth)acrylate compound with a polyvalent isocyanate compound and a polyol compound may be used. Among these, a compound obtained by reacting a hydroxyl group-containing (meth)acrylate compound with a polyvalent isocyanate compound and a polyol compound is preferred from the viewpoint of realizing high impact resistance.
[0015] Examples of the hydroxyl group-containing (meth)acrylate compound include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate. acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl(meth)acrylate, glycerin di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, etc. These hydroxyl group-containing (meth)acrylate compounds may be used alone or in combination of two or more.
[0016] Examples of the polyisocyanate-based compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of the polyisocyanate include aliphatic polyisocyanates such as isocyanate and lysine triisocyanate, alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane, as well as trimer compounds or polymer compounds of these polyisocyanates, allophanate-type polyisocyanates, biuret-type polyisocyanates, and water-dispersible polyisocyanates. These polyisocyanate compounds may be used alone or in combination of two or more.
[0017] Examples of the polyol-based compound include polyether-based polyols, polyester-based polyols, polycarbonate-based polyols, polyolefin-based polyols, polybutadiene-based polyols, (meth)acrylic-based polyols, polysiloxane-based polyols, etc. These polyol-based compounds may be used alone or in combination of two or more kinds.
[0018] Examples of the polyether polyol include alkylene structure-containing polyether polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, and polyhexamethylene glycol, and random or block copolymers of these polyalkylene glycols.
[0019] Examples of the polyester polyol include a condensation polymer of a polyhydric alcohol and a polycarboxylic acid, a ring-opening polymer of a cyclic ester (lactone), and a reaction product of three components: a polyhydric alcohol, a polycarboxylic acid, and a cyclic ester.
[0020] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol).
[0021] Examples of the polyvalent carboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid.
[0022] Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.
[0023] Examples of the polycarbonate-based polyol include a reaction product of a polyhydric alcohol with phosgene, and a ring-opening polymer of a cyclic carbonate (such as an alkylene carbonate).
[0024] Examples of the polyhydric alcohol as the polycarbonate-based polyol include the polyhydric alcohols exemplified in the description of the polyester-based polyol, and examples of the alkylene carbonate include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate.
[0025] The polycarbonate-based polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.
[0026] The weight average molecular weight of the polyfunctional urethane (meth)acrylate (A) in the curable resin composition of this embodiment is preferably 1000 or more and 60000 or less. More preferably, it is 2000 or more and 50000 or less. When the weight average molecular weight is 1000 or more, the impact resistance of the cured product tends to increase significantly with a decrease in crosslink density, which is preferable. When the weight average molecular weight is more than 60000, the viscosity of the curable composition increases, which tends to make it difficult to handle, which is not preferable.
[0027] The weight average molecular weight (Mw) of the polyfunctional urethane (meth)acrylate (A) is the weight average molecular weight calculated based on the molecular weight of standard polystyrene. The weight average molecular weight was measured by a high performance liquid chromatography (Tosoh Corporation, high-speed GPC device "HLC-8220GPC") using a column: Shodex GPCLF-804 (exclusion limit molecular weight: 2 × 10 6 , Separation range: 300~2×10 6 ) in series.
[0028] The polyfunctional urethane (meth)acrylate (A) preferably has a radical polymerizable functional group equivalent of 400 g / eq or more. In this embodiment, the radical polymerizable functional group equivalent is a value indicating the molecular weight per one radical polymerizable functional group. If the radical polymerizable functional group equivalent is less than 400 g / eq, the impact resistance tends to decrease with an increase in crosslink density, which is not preferable.
[0029] The content of the polyfunctional urethane (meth)acrylate (A) in the curable resin composition of this embodiment is preferably 5 parts by mass or more and 70 parts by mass or less with respect to 100 parts by mass of the total of the polyfunctional urethane (meth)acrylate (A) and other radical polymerizable compounds. More preferably, it is 10 parts by mass or more and 60 parts by mass or less. By having the content of the polyfunctional urethane (meth)acrylate (A) within the above-mentioned range, it is possible to achieve both high impact resistance and heat resistance. If the content of the polyfunctional urethane (meth)acrylate (A) is less than 5 parts by mass, the impact resistance tends to decrease. In addition, if the content of the polyfunctional urethane (meth)acrylate is more than 70 parts by mass, the heat resistance tends to decrease and the viscosity of the resin composition tends to be higher than the range suitable for materials for stereolithography.
[0030] <Hydrophilic monofunctional radically polymerizable compound (B)> The hydrophilic monofunctional radical polymerizable compound (B) contained in the curable resin composition of the present embodiment is a compound having one radical polymerizable functional group in the molecule and exhibiting water solubility. In the present invention, the hydrophilic monofunctional radical polymerizable compound refers to a compound having a solubility in water of 2.5 [g / 100 g] or more. Herein, the solubility in water represents the amount of the hydrophilic monofunctional radical polymerizable compound (B) that can be dissolved in 100 g of water at 25°C. Hereinafter, the hydrophilic monofunctional radical polymerizable compound (B) may be simply referred to as compound (B).
[0031] The radical polymerizable functional group may be an ethylenically unsaturated group. Specifically, the ethylenically unsaturated group may be a (meth)acryloyl group, a vinyl group, etc. In this specification, the (meth)acryloyl group means an acryloyl group or a methacryloyl group.
[0032] Examples of the hydrophilic monofunctional radically polymerizable compound (B) having a (meth)acryloyl group include hydrophilic monofunctional acrylamide compounds and hydrophilic monofunctional (meth)acrylate compounds.
[0033] Examples of hydrophilic monofunctional acrylamide compounds include (meth)acrylamide, N-methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methylol(meth)acrylamide, diacetone(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-(meth)acryloylmorpholine, and N-[3-(dimethylamino)propyl]acrylamide.
[0034] Examples of hydrophilic monofunctional (meth)acrylate compounds include (meth)acrylic acid, methyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, dimethylaminomethyl (meth)acrylate, 2-hydroxyethyl (meth)acryloyl phosphate, methoxypolyethylene glycol methacrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-diethylaminoethyl (meth)acrylate.
[0035] Examples of hydrophilic monofunctional radical polymerizable compounds having a vinyl group include vinyl acetate and hydrophilic N-vinyl compounds, such as N-vinylpyrrolidone, N-vinylcaprolactam, and N-vinylacetamide.
[0036] Other examples of hydrophilic monofunctional radically polymerizable compounds include styrene derivatives such as styrenesulfonic acid and its salts, and vinyl cyanide compounds such as (meth)acrylonitrile.
[0037] These hydrophilic monofunctional radically polymerizable compounds may be used alone or in combination of two or more kinds.
[0038] From the viewpoint of dimensional stability of the cured product, the preferred range of the content of the hydrophilic monofunctional radical polymerizable compound (B) in the curable resin composition of this embodiment varies depending on the solubility of the hydrophilic monofunctional radical polymerizable compound (B) in water. When the solubility of the hydrophilic monofunctional radical polymerizable compound (B) in water is 20 [g / 100g] or more, the content is preferably 55 parts by mass or less, more preferably 50 parts by mass or less, relative to 100 parts by mass in total with the radical polymerizable compound. When the content of the hydrophilic monofunctional radical polymerizable compound having a solubility in water of 20 [g / 100g] or more is more than 55 parts by mass, the water absorption rate of the cured product of the curable resin composition becomes high. Therefore, when exposed to a high humidity environment, the dimensional change tends to exceed the allowable range due to water absorption. In addition, when the solubility of the hydrophilic monofunctional radical polymerizable compound (B) in water is less than 20 [g / 100g], the content in the curable resin composition is preferably 65 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass in total with the radical polymerizable compound. When the curable resin composition contains both a compound having a solubility in water of 20 [g / 100g] or more and a compound having a solubility in water of less than 20 [g / 100g] as the hydrophilic monofunctional radical polymerizable compound (B), the upper limit of the content of the compound (B) can be calculated by the following formula. That is, when the total amount of the hydrophilic monofunctional radical polymerizable compounds is 100 parts by mass, and the content ratio of the hydrophilic monofunctional radical polymerizable compounds having a solubility in water of 20 [g / 100g] or more is X parts by mass, the upper limit can be calculated as (55 x X + 65 x (100 - X)) / 100 [parts by mass].
[0039] In addition, when the curable resin composition is used for stereolithography, the content of the hydrophilic monofunctional radical polymerizable compound (B) in the curable resin composition of the present embodiment is preferably 10 parts by mass or more, regardless of the solubility in water, from the viewpoint of viscosity. More preferably, it is 15% by mass or more. When the content of the hydrophilic monofunctional radical polymerizable compound (B) is 10 parts by mass or more, the viscosity increase of the curable resin composition when the rubber particles (D) are added tends to be mitigated, which is preferable.
[0040] That is, the preferred range of the content of the hydrophilic monofunctional radically polymerizable compound (B) in the curable resin composition is 10 parts by mass or more and 65 parts by mass or less, more preferably 15 parts by mass or more and 55 parts by mass or less, relative to 100 parts by mass in total of the hydrophilic monofunctional radically polymerizable compound (B) and the radically polymerizable compound.
[0041] <Hydrophobic monofunctional radically polymerizable compound (C)> In the present invention, the hydrophobic monofunctional radically polymerizable compound (C) contained in the curable resin composition refers to a compound having one radically polymerizable functional group in the molecule and having a solubility in water of less than 2.5 [g / 100 g].
[0042] The radical polymerizable functional group may be an ethylenically unsaturated group. Specifically, the ethylenically unsaturated group may be a (meth)acryloyl group, a vinyl group, etc. In this specification, the (meth)acryloyl group means an acryloyl group or a methacryloyl group.
[0043] Examples of the hydrophobic monofunctional radically polymerizable compound having a (meth)acryloyl group include hydrophobic monofunctional acrylamide compounds and hydrophobic monofunctional (meth)acrylate compounds.
[0044] Examples of the hydrophobic monofunctional acrylamide compound include N-tert-butyl(meth)acrylamide, N-phenyl(meth)acrylamide, and N-(meth)acryloylpiperidine.
[0045] Examples of the hydrophobic monofunctional (meth)acrylate compound include methyl methacrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (Meth)acrylate, 3-hydroxy-1-adamantyl (meth)acrylate, 3,5-dihydroxy-1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 2-isopropyl-2-adamantyl (meth)acrylate, glycidyl (meth)acrylate, 3-methyl-3-oxetanyl-methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenylglycidyl (meth)acrylate acrylate, phenyl cellosolve (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, biphenyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, benzyl (meth)acrylate, trifluoromethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, octafluoropentyl acrylate acrylate, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, allyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H,octafluoropentyl (meth)acrylate, methyl allyloxyacrylate (product name: AO-MA, manufactured by Nippon Shokubai Co., Ltd.), (meth)acrylates having an imide group (product name: M-140, manufactured by Toagosei Co., Ltd.), and the like.
[0046] Examples of hydrophobic monofunctional radically polymerizable compounds having an ethylenically unsaturated group other than those mentioned above include styrene derivatives such as styrene, vinyltoluene, α-methylstyrene, and chlorostyrene; maleimides such as ethylmaleimide, propylmaleimide, butylmaleimide, hexylmaleimide, octylmaleimide, dodecylmaleimide, stearylmaleimide, phenylmaleimide, and cyclohexylmaleimide; vinyl esters such as vinyl propionate, vinyl pivalate, vinyl benzoate, and vinyl cinnamate; and N-vinyl compounds such as N-vinylphthalimide and N-vinylcarbazole.
[0047] Considering the dimensional stability of the article produced by curing the curable resin composition, the content of the hydrophobic monofunctional radical polymerizable compound (C) in the curable resin composition is preferably 5 parts by mass or more relative to 100 parts by mass of the total of the radical polymerizable compound and the hydrophobic monofunctional radical polymerizable compound (C). More preferably, it is 10 parts by mass or more. If the content of the hydrophobic monofunctional radical polymerizable compound is less than 5 parts by mass, the water absorption rate increases, and the dimensional change tends to exceed the allowable range due to water absorption in a high humidity environment. In other words, it is preferable that the water absorption rate is such that the dimensional change does not exceed the allowable range and does not cause a large change in mechanical properties.
[0048] When a compound having an alicyclic hydrocarbon group is used as the hydrophobic monofunctional radical polymerizable compound (C), the content is preferably less than 60 parts by mass relative to the total of 100 parts by mass of the radical polymerizable compound of this embodiment. More preferably, it is 55 parts by mass or less. If the content of the hydrophobic monofunctional radical polymerizable compound having an alicyclic hydrocarbon group is 60 parts by mass or more, the viscosity of the curable resin composition when the rubber particles (D) are added increases, and handling tends to become difficult. For example, when the curable resin composition is used as a modeling material for a stereolithography method, the modeling time may be extended or the modeling itself may become difficult due to the increase in viscosity.
[0049] Examples of the hydrophobic monofunctional radically polymerizable compound having an alicyclic hydrocarbon group include isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-t-butylcyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0050] The glass transition temperature (Tg) of the copolymer of the mixture of the hydrophobic monofunctional radical polymerizable compound (C) and the hydrophilic monofunctional radical polymerizable compound (B) is preferably 85° C. or higher. More preferably, it is 90° C. or higher. The Tg of the copolymer can be determined by the FOX formula (formula (1)). The unit of Tg is absolute temperature. 1 / Tg=Σ(Wi / Tgi) Equation (1)
[0051] In the above formula (1), Wi is the mass ratio of each of the hydrophilic and hydrophobic monofunctional radical polymerizable compounds in the copolymer. Tgi is the glass transition temperature (unit: absolute temperature) of each homopolymer of the hydrophilic and hydrophobic radical polymerizable compounds. Details of the FOX formula are described in Bulletin of the American Physical Society, Series 2, Vol. 1, No. 3, p. 123 (1956). The glass transition temperature (Tgi) of each homopolymer of various radical polymerizable compounds used in the FOX formula can be a commonly known value for each polymer. Alternatively, the polymer may be actually prepared and the actual measured value obtained by differential scanning calorimetry (DSC) or dynamic viscoelasticity measurement (DMA) may be used.
[0052] Hereinafter, the hydrophilic monofunctional radical polymerizable compound (B) and the hydrophobic monofunctional radical polymerizable compound (C) are collectively referred to as monofunctional radical polymerizable compound (B+C). The content of the monofunctional radical polymerizable compound (B+C) is preferably 30 parts by mass or more and 90 parts by mass or less, more preferably 50 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the radical polymerizable compound.
[0053] <Rubber particles (D)> By incorporating the rubber particles (D) in the curable resin composition, the impact resistance of the cured product can be improved.
[0054] The type of rubber particles is not particularly limited. Examples of preferred compositions constituting the rubber particles include butadiene rubber, styrene / butadiene copolymer rubber, acrylonitrile / butadiene copolymer rubber, saturated rubber obtained by hydrogenating or partially hydrogenating these diene rubbers, crosslinked butadiene rubber, isoprene rubber, chloroprene rubber, natural rubber, silicone rubber, ethylene / propylene / diene monomer terpolymer rubber, acrylic rubber, and acrylic / silicone composite rubber. The rubber particles are preferably composed of these compositions alone or in combination of two or more. Among them, from the viewpoint of improving impact resistance and suppressing the increase in viscosity of the curable resin composition, rubber particles made of any one of butadiene rubber, crosslinked butadiene rubber, styrene / butadiene copolymer rubber, acrylic rubber, and silicone / acrylic composite rubber are particularly preferred.
[0055] The glass transition temperature of the rubber particle composition is preferably 25° C. or lower. More preferably, it is 20° C. or lower. If the glass transition temperature is higher than 25° C., it tends to be difficult to obtain an effect of improving impact resistance. The glass transition temperature of the rubber particle composition can be determined, for example, by differential scanning calorimetry (DSC) or dynamic viscoelasticity measurement (DMA).
[0056] The rubber particles are more preferably rubber particles having a core-shell structure. Specifically, the rubber particles preferably have the above-mentioned rubber particles as a core and a shell made of a polymer of a radical polymerizable compound that coats the outside of the core. By using rubber particles having a core-shell structure, the dispersibility of the rubber particles in a resin composition containing a multifunctional urethane (meth)acrylate (A), a hydrophilic monofunctional radical polymerizable compound (B), and a hydrophobic monofunctional radical polymerizable compound (C) can be improved. As a result, a cured product in which the rubber particles are uniformly dispersed can be obtained, and the rubber particles can function effectively in the cured product to further improve impact resistance.
[0057] The polymer of the radical polymerizable compound forming the shell is preferably graft polymerized onto the surface of the core via a chemical bond, and has a form that covers a part or the whole of the core. The rubber particles having a core-shell structure in which the shell is graft polymerized onto the core can be formed by graft polymerizing the radical polymerizable compound by a known method in the presence of the core particles. For example, the rubber particles can be produced by adding the radical polymerizable compound, which is a component of the shell, to latex particles dispersed in water, which can be prepared by emulsion polymerization, mini-emulsion polymerization, suspension polymerization, seed polymerization, etc., and polymerizing the resulting mixture.
[0058] In addition, when the surface of the core does not have or has very few reactive sites such as ethylenically unsaturated groups that can be graft-polymerized with the shell, an intermediate layer containing reactive sites may be provided on the surface of the core particle, and then the shell may be graft-polymerized. That is, the form of the rubber particle having a core-shell structure also includes a form in which the shell is provided on the core via an intermediate layer.
[0059] The above-mentioned compositions can be used as the composition constituting the core of the rubber particles having a core-shell structure. Since the softer the rubber particles are, the better the impact resistance is expected to be, it is particularly preferable to use at least one of butadiene rubber, crosslinked butadiene rubber, styrene / butadiene copolymer rubber, acrylic rubber, and silicone / acrylic composite rubber as the core.
[0060] As the radical polymerizable compound forming the shell, a monofunctional radical polymerizable compound having one radical polymerizable functional group in the molecule can be suitably used. The rubber particles having a shell containing a polymer of the monofunctional radical polymerizable compound have excellent dispersibility when dispersed in a resin composition containing the radical polymerizable compound.
[0061] The monofunctional radical polymerizable compound used to form the shell can be appropriately selected in consideration of compatibility with the composition constituting the core and dispersibility in the resin composition. For example, one or more of the materials exemplified as the hydrophilic monofunctional radical polymerizable compound (B) and the hydrophobic monofunctional radical polymerizable compound (C) may be used in combination. If the shell contains a polymer of a monofunctional radical polymerizable compound having a (meth)acryloyl group, the dispersion of the rubber particles in the curable resin composition is good, and the increase in viscosity of the curable resin composition can be suppressed, which is preferable. Among them, rubber particles having a shell containing a polymer of a hydrophobic monofunctional radical polymerizable compound having a (meth)acryloyl group are particularly preferable.
[0062] In addition, as the radical polymerizable compound for forming the shell, a monofunctional radical polymerizable compound and a polyfunctional radical polymerizable compound may be used in combination. When the shell is formed using a polyfunctional radical polymerizable compound, the viscosity of the curable resin composition tends to be low and easy to handle. On the other hand, when the content of the polyfunctional radical polymerizable compound becomes excessive, the effect of improving the impact resistance by adding rubber particles having a core-shell structure tends to be difficult to obtain. Therefore, the polyfunctional radical polymerizable compound used for forming the shell is preferably 0 parts by mass or more and 40 parts by mass or less with respect to 100 parts by mass of the radical polymerizable compound used for forming the shell. Furthermore, 0 parts by mass or more and 30 parts by mass or less are more preferable, and 0 parts by mass or more and 25 parts by mass or less are particularly preferable. The polyfunctional radical polymerizable compound used for forming the shell can be appropriately selected in consideration of the compatibility with the composition constituting the core and the dispersibility in the resin composition. One or more of the polyfunctional urethane (meth)acrylate (A) and the materials exemplified later as the polyfunctional radical polymerizable compound may be used in combination.
[0063] The mass ratio of the core to the shell in the rubber particles having a core-shell structure is preferably 1 part by mass or more and 200 parts by mass or less of the shell relative to 100 parts by mass of the core, more preferably 2 parts by mass or more and 180 parts by mass or less. If the mass ratio of the core to the shell is within the above range, it is possible to effectively improve the impact resistance by including the rubber particles. If the shell is less than 1 part by mass, the dispersibility of the rubber particles in the curable resin composition is not sufficient, so that it is difficult to obtain the effect of improving the impact resistance. In addition, if the shell is more than 200 parts by mass, the dispersibility in the curable resin composition is excellent, but the rubber particles are thickly covered with the shell, so that the effect of improving the impact resistance by the rubber component is reduced. Therefore, in order to obtain sufficient impact resistance, it is necessary to add a large amount of rubber particles, and the viscosity of the curable resin composition tends to increase, making it difficult to handle.
[0064] The average particle size of the rubber particles is preferably 20 nm or more and 10 μm or less, more preferably 50 nm or more and 5 μm or less. If the average particle size is less than 20 nm, the viscosity of the curable resin composition increases with the addition of the rubber particles, and the interaction between the rubber particles occurs with the increase in the specific surface area of the rubber particles, which tends to cause a decrease in the heat resistance and impact resistance of the cured product. In addition, if the average particle size is more than 10 μm, the rubber particles (rubber component) become difficult to disperse in the curable resin composition, and the effect of improving impact resistance by adding the rubber particles tends to decrease.
[0065] The average particle size of the rubber particles in the present invention is an arithmetic (number) average particle size, which can be measured by a dynamic light scattering method. For example, the rubber particles can be dispersed in an appropriate organic solvent and measured by a particle size distribution meter.
[0066] In addition, the gel fraction of the rubber particles is preferably 5% or more. If the gel fraction is less than 5%, it is not preferable because both the impact resistance and the heat resistance tend to decrease. The gel fraction can be calculated by the following procedure. Dried rubber particles W1 [g] are immersed in a sufficient amount of toluene and left at room temperature for 7 days. Thereafter, the solid content is taken out by centrifugation or the like and dried at 100°C for 2 hours, and the amount of the solid content obtained after drying is measured. If the mass of the solid content obtained after drying is W2 [g], it can be calculated by the following formula. Gel fraction (%) = W2 / W1 × 100
[0067] The content of rubber particles in the curable resin composition is 8 parts by mass or more and 50 parts by mass or less, based on 100 parts by mass of the total of radical polymerizable compounds. It is preferably 10 parts by mass or more and 40 parts by mass or less. If the content of rubber particles is less than 8 parts by mass, the effect of improving impact resistance by adding rubber particles cannot be obtained. If the content of rubber particles is more than 50 parts by mass, the heat resistance of the obtained cured product is significantly reduced. In addition, the viscosity of the curable resin composition increases significantly, making it difficult to handle.
[0068] <Radical polymerization initiator (E)> As the radical polymerization initiator (E), a photoradical polymerization initiator or a thermal radical polymerization initiator can be used.
[0069] The photoradical polymerization initiators are mainly classified into intramolecular cleavage type and hydrogen abstraction type. In the intramolecular cleavage type photoradical polymerization initiator, a bond at a specific site is cut by absorbing light of a specific wavelength, and a radical is generated at the cut site, which becomes a polymerization initiator and starts the polymerization of an ethylenically unsaturated compound containing a (meth)acryloyl group. On the other hand, in the case of the hydrogen abstraction type, a light of a specific wavelength is absorbed and becomes excited, and the excited species causes a hydrogen abstraction reaction from a hydrogen donor in the vicinity, generating a radical, which becomes a polymerization initiator and starts the polymerization of a radically polymerizable compound.
[0070] Known examples of the intramolecular cleavage type photoradical polymerization initiator include alkylphenone-based photoradical polymerization initiators, acylphosphine oxide-based photoradical polymerization initiators, and oxime ester-based photoradical polymerization initiators. These are types in which the bond adjacent to the carbonyl group undergoes α-cleavage to generate radical species. Examples of the alkylphenone-based photoradical polymerization initiator include benzyl methyl ketal-based photoradical polymerization initiators, α-hydroxyalkylphenone-based photoradical polymerization initiators, and aminoalkylphenone-based photoradical polymerization initiators. Specific examples of compounds include benzyl methyl ketal-based photoradical polymerization initiators such as 2,2'-dimethoxy-1,2-diphenylethan-1-one (Irgacure (registered trademark) 651, manufactured by BASF), and α-hydroxyalkylphenone-based photoradical polymerization initiators such as 2-hydroxy-2-methyl-1-phenylpropan-1-one (Darocure 1173, manufactured by BASF), 1-hydroxycyclohexyl phenyl ketone (Irgacure 184, manufactured by BASF), 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (Irgacure 185, manufactured by BASF), and 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (Irgacure 186, manufactured by BASF). Examples of the aminoalkylphenone-based photoradical polymerization initiator include, but are not limited to, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (Irgacure 907, BASF) and 2-benzylmethyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone (Irgacure 369, BASF). Examples of the acylphosphine oxide-based photoradical polymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Lucirin TPO, manufactured by BASF), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure 819, manufactured by BASF), and the like, but are not limited thereto.Examples of oxime ester photoradical polymerization initiators include, but are not limited to, (2E)-2-(benzoyloxyimino)-1-[4-(phenylthio)phenyl]octan-1-one (Irgacure OXE-01, manufactured by BASF). An example of the trade name is shown in parentheses.
[0071] Examples of the hydrogen abstraction type radical polymerization initiator include anthraquinone derivatives such as 2-ethyl-9,10-anthraquinone and 2-t-butyl-9,10-anthraquinone, and thioxanthone derivatives such as isopropylthioxanthone and 2,4-diethylthioxanthone, but are not limited thereto. These photoradical polymerization initiators may be used alone or in combination of two or more kinds. They may also be used in combination with a thermal radical polymerization initiator described later.
[0072] The amount of the photoradical polymerization initiator added is preferably 0.1 to 15 parts by mass relative to 100 parts by mass of the radical polymerizable compound contained in the curable resin composition. More preferably, it is 0.1 to 10 parts by mass. If the amount of the photoradical polymerization initiator is small, polymerization tends to be insufficient. If an excessive amount of the polymerization initiator is added, the molecular weight does not increase, and there is a risk that the heat resistance or impact resistance will decrease. Here, the radical polymerizable compound is a combination of the multifunctional urethane (meth)acrylate (A), the monofunctional radical polymerizable compound (B+C), and other multifunctional radical polymerizable compounds.
[0073] The thermal radical polymerization initiator is not particularly limited as long as it generates radicals by heating, and conventionally known compounds can be used. For example, preferred examples include azo compounds, peroxides, and persulfates. Examples of azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(methylisobutyrate), 2,2'-azobis-2,4-dimethylvaleronitrile, and 1,1'-azobis(1-acetoxy-1-phenylethane). Examples of peroxides include benzoyl peroxide, di-t-butylbenzoyl peroxide, t-butyl peroxypivalate, and di(4-t-butylcyclohexyl)peroxydicarbonate. Examples of persulfates include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.
[0074] The amount of the thermal radical polymerization initiator added is preferably 0.1 to 15 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the radical polymerizable compound contained in the curable resin composition. If an excessive amount of the polymerization initiator is added, the molecular weight does not increase, and the heat resistance or impact resistance may decrease.
[0075] <Other ingredients (F)> The curable resin composition may contain other components as long as the objects and effects of the present invention are not impaired.
[0076] Examples of the other components include polyfunctional radically polymerizable compounds other than the polyfunctional urethane (meth)acrylate (A) and additives.
[0077] First, the case where a polyfunctional radically polymerizable compound other than the polyfunctional urethane (meth)acrylate (A) is contained will be described.
[0078] When the composition contains a polyfunctional radically polymerizable compound having a radically polymerizable functional group equivalent of less than 300 g / eq, the content is preferably 20 parts by mass or less relative to 100 parts by mass of the total radically polymerizable compounds contained in the curable resin composition. More preferably, the content is 18 parts by mass or less. The radically polymerizable functional group equivalent is a value indicating the molecular weight per one radically polymerizable functional group.
[0079] If the content of the polyfunctional radically polymerizable compound with a radically polymerizable functional group equivalent of less than 300 g / eq is more than 20 parts by mass, the crosslink density of the cured product tends to increase and become non-uniform at the same time. As a result, when an impact is applied from the outside, there are areas where stress is concentrated, and the expected effect of improving impact resistance by adding rubber particles cannot be obtained, and the Charpy impact strength may become the same as that of the conventional technology.
[0080] When a polyfunctional radical polymerizable compound having a radical polymerizable functional group equivalent of 300 g / eq or more is contained, the content is preferably less than 50 parts by mass relative to 100 parts by mass of the total radical polymerizable compounds contained in the curable resin composition. If the content of the polyfunctional radical polymerizable compound having a radical polymerizable functional group equivalent of 300 g / eq or more is more than 50 parts by mass, the heat resistance decreases and the crosslink density of the cured product increases, and it tends to be difficult to obtain the effect of improving impact resistance expected from the addition of rubber particles.
[0081] The radical polymerizable functional group of the polyfunctional radical polymerizable compound other than the polyfunctional urethane (meth)acrylate (A) may be an ethylenically unsaturated group. The ethylenically unsaturated group may be a (meth)acryloyl group, a vinyl group, etc. The polyfunctional radical polymerizable compound may be, for example, a polyfunctional (meth)acrylate-based compound, a vinyl ether group-containing (meth)acrylate-based compound, a polyfunctional (meth)acryloyl group-containing isocyanurate-based compound, a polyfunctional (meth)acrylamide-based compound, a polyfunctional maleimide-based compound, a polyfunctional vinyl ether-based compound, a polyfunctional aromatic vinyl-based compound, etc.
[0082] Examples of the polyfunctional (meth)acrylate compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4 butanediol di(meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6- Hexamethylene di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, di(meth)acrylate of hydroxypivalic acid neopentyl glycol ε-caprolactone adduct (e.g., KAYARAD, manufactured by Nippon Kayaku Co., Ltd.) HX-220, HX-620, etc.), di(meth)acrylates of EO adducts of bisphenol A, multifunctional (meth)acrylates having fluorine atoms, multifunctional (meth)acrylates having a siloxane structure, polycarbonate diol di(meth)acrylate, polyester di(meth)acrylate, polyethylene glycol di(meth)acrylate, etc.
[0083] Examples of the vinyl ether group-containing (meth)acrylate compound include 2-vinyloxyethyl (meth)acrylate, 4-vinyloxybutyl (meth)acrylate, 4-vinyloxycyclohexyl (meth)acrylate, 2-(vinyloxyethoxy)ethyl (meth)acrylate, and 2-(vinyloxyethoxyethoxyethoxy)ethyl (meth)acrylate.
[0084] Examples of the polyfunctional (meth)acryloyl group-containing isocyanurate compound include tri(acryloyloxyethyl)isocyanurate, tri(methacryloyloxyethyl)isocyanurate, and ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate.
[0085] Examples of the polyfunctional (meth)acrylamide compound include N,N'-methylenebisacrylamide, N,N'-ethylenebisacrylamide, N,N'-(1,2-dihydroxyethylene)bisacrylamide, N,N'-methylenebismethacrylamide, and N,N',N''-triacryloyldiethylenetriamine.
[0086] Examples of the polyfunctional maleimide compounds include 4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, and 1,6-bismaleimide-(2,2,4-trimethyl)hexane.
[0087] Examples of the polyfunctional vinyl ether compound include ethylene glycol divinyl ether, diethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, butylene glycol divinyl ether, hexanediol divinyl ether, bisphenol A alkylene oxide divinyl ether, bisphenol F alkylene oxide divinyl ether, trimethylolpropane trivinyl ether, ditrimethylolpropane tetravinyl ether, glycerin trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, and dipentaerythritol hexavinyl ether.
[0088] Examples of the polyfunctional aromatic vinyl compounds include divinylbenzene.
[0089] These polyfunctional radically polymerizable compounds may be used alone or in combination of two or more kinds.
[0090] Examples of the additives include property modifiers for imparting desired physical properties to the cured product, photosensitizers, polymerization initiation assistants, leveling agents, wettability improvers, surfactants, plasticizers, ultraviolet absorbers, silane coupling agents, inorganic fillers, pigments, dyes, antioxidants, flame retardants, thickeners, and defoamers.
[0091] The amount of the additive is preferably 0.05 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the total of the polyfunctional urethane (meth)acrylate (A), the monofunctional radical polymerizable compound (B+C), and the other polyfunctional radical polymerizable compound. More preferably, it is 0.1 parts by mass or more and 20 parts by mass or less. Within this range, the desired physical properties can be imparted to the cured product or the curable resin composition without decreasing the impact resistance or increasing the water absorption rate of the obtained cured product.
[0092] For example, physical property modifiers for imparting desired physical properties to the cured product include resins such as epoxy resins, polyurethanes, polychloroprene, polyesters, polysiloxanes, petroleum resins, xylene resins, ketone resins, and cellulose resins, as well as polycarbonates, modified polyphenylene ethers, polyamides, polyacetals, polyethylene terephthalates, polybutylene terephthalates, ultra-high molecular weight polyethylenes, polyphenylsulfones, polysulfones, polyarylates, polyetherimides, polyetheretherketones, polyphenylenes, and the like. Examples of the material include engineering plastics such as polystyrene sulfide, polyethersulfone, polyamideimide, liquid crystal polymers, polytetrafluoroethylene, polychlorotrifluoroethylene, and polyvinylidene fluoride, fluorine-based oligomers, silicone-based oligomers, polysulfide-based oligomers, soft metals such as gold, silver, and lead, and layered crystal structure materials such as graphite, molybdenum disulfide, tungsten disulfide, boron nitride, graphite fluoride, calcium fluoride, barium fluoride, lithium fluoride, silicon nitride, and molybdenum selenide.
[0093] Examples of photosensitizers include polymerization inhibitors such as phenothiazine and 2,6-di-t-butyl-4-methylphenol, benzoin compounds, acetophenone compounds, anthraquinone compounds, thioxanthone compounds, ketal compounds, benzophenone compounds, tertiary amine compounds, and xanthone compounds.
[0094] <Curable resin composition> The curable resin composition is prepared by adding appropriate amounts of the polyfunctional urethane (meth)acrylate (A), the monofunctional radical polymerizable compound (B+C), the rubber particles (D), the radical polymerization initiator (E), and other components as required, to a stirring vessel and stirring them. The stirring temperature is usually 20°C or higher and 120°C or lower, preferably 40°C or higher and 100°C or lower. The composition can be produced by removing volatile solvents and the like as required.
[0095] The curable resin composition according to the present invention can be suitably used as a modeling material for use in stereolithography. That is, a modeled object having a desired shape can be produced by selectively irradiating the curable resin composition of the present embodiment with active energy rays to supply the energy required for curing. When the curable resin composition of the present embodiment is used as a modeling material for stereolithography, the viscosity at 25°C is preferably 50 mPa·s or more and 5,000 mPa·s or less, more preferably 75 mPa·s or more and 4,500 mPa·s or less.
[0096] <Production method> The cured product (modeled product) obtained by curing the curable resin composition according to the present invention can be produced using a known stereolithography method and device. A representative example of a preferred stereolithography method is a method having a step of repeatedly curing the curable resin composition to a predetermined thickness based on slice data generated from three-dimensional shape data of the object to be manufactured (modeled model). There are two main types: the free liquid level method and the restricted liquid level method.
[0097] Fig. 1 shows an example of the configuration of a photo-fabrication apparatus 100 using the free liquid surface method. The photo-fabrication apparatus 100 has a tank 11 filled with a liquid photocurable resin composition 10. Inside the tank 11, a modeling stage 12 is provided so as to be drivable in the vertical direction by a drive shaft 13. The irradiation position of a light energy beam 15 for curing the photocurable resin composition 10 emitted from a light source 14 is changed by a galvanometer mirror 16 controlled by a control unit 18 according to slice data, and the surface of the tank 11 is scanned. In Fig. 1, the scanning range is indicated by a thick dashed line.
[0098] The thickness d of the photocurable resin composition 10 cured by the light energy beam 15 is a value determined based on the settings at the time of generating the slice data, and affects the accuracy of the obtained object (reproducibility of the three-dimensional shape data of the object to be molded). The thickness d is achieved by the control unit 18 controlling the drive amount of the drive shaft 13.
[0099] First, the control unit 18 controls the drive shaft 13 based on the settings, and the photocurable resin composition is supplied to the stage 12 at a thickness d. The liquid curable resin composition on the stage 12 is selectively irradiated with light energy rays based on slice data so as to obtain a cured layer having a desired pattern, and a cured layer is formed. Next, the stage 12 is moved in the direction of the white arrow, and an uncured curable resin composition is supplied to the surface of the cured layer at a thickness d. Then, light energy rays 15 are irradiated based on the slice data, and a cured product integrated with the previously formed cured layer is formed. By repeating this layer-by-layer curing process, a desired three-dimensional object can be obtained.
[0100] The three-dimensional object thus obtained is taken out of the tank 11, and the unreacted curable resin composition remaining on the surface is removed, and then washed as necessary. As the washing agent, an alcohol-based organic solvent, such as alcohols such as isopropyl alcohol and ethyl alcohol, can be used. In addition, a ketone-based organic solvent, such as acetone, ethyl acetate, methyl ethyl ketone, or an aliphatic organic solvent, such as terpenes, can be used. After washing with the washing agent, post-curing by light irradiation or heat irradiation can be performed as necessary. Post-curing can cure the unreacted curable resin composition that may remain on the surface and inside of the three-dimensional object, and can suppress the stickiness of the surface of the three-dimensional object, as well as improve the initial strength of the three-dimensional object.
[0101] Examples of light energy rays used in the production of three-dimensional objects include ultraviolet rays, electron beams, X-rays, and radiation. Among these, ultraviolet rays having a wavelength of 300 nm or more and 450 nm or less are preferably used from an economical point of view. Examples of light sources that generate ultraviolet rays include ultraviolet lasers (e.g., Ar lasers, He-Cd lasers, etc.), mercury lamps, xenon lamps, halogen lamps, and fluorescent lamps. Among these, laser light sources are preferably used because they have excellent light-collecting properties, can increase the energy level to shorten the modeling time, and can obtain high modeling accuracy.
[0102] When irradiating a surface made of a curable resin composition with active energy rays to form a cured layer having a predetermined pattern, the resin can be cured by a pointillist or line drawing method using light energy rays focused in a dotted or line shape. Alternatively, the resin can be cured by irradiating the active energy rays in a planar manner through a planar drawing mask formed by arranging a plurality of microscopic light shutters such as liquid crystal shutters or digital micromirror shutters.
[0103] Similarly, modeling by the regulated liquid level method is also preferable. In the optical modeling apparatus using the regulated liquid level method, the stage 12 of the optical modeling apparatus 100 in FIG. 1 is provided so as to raise the model above the liquid level, and the light irradiation means is provided below the tank 11. A typical modeling example by the regulated liquid level method is as follows. First, the support surface of the support stage, which is provided so as to be freely raised and lowered, and the bottom surface of the tank containing the curable resin composition are set at a predetermined distance, and the curable resin composition is supplied between the support surface of the support stage and the bottom surface of the tank. Next, light is selectively irradiated from the bottom surface side of the tank containing the curable resin composition to the curable resin composition between the stage support surface and the bottom surface of the tank according to slice data by a laser light source or a projector. The curable resin composition between the stage support surface and the bottom surface of the tank is cured by the irradiation of light, and a solid cured resin layer is formed. After that, the support stage is raised, and the cured resin layer is peeled off from the bottom surface of the tank.
[0104] Next, the height of the support stage is adjusted so that the distance between the cured layer formed on the support stage and the bottom surface of the tank is a predetermined distance. Then, by selectively irradiating light in the same manner as above, a new cured resin layer is formed between the cured resin layer and the bottom surface of the tank, which is integrated with the previously formed cured resin layer. This process is then repeated a predetermined number of times, with or without changing the light irradiation pattern, to form a three-dimensional object in which multiple cured resin layers are stacked together. EXAMPLES
[0105] The present embodiment will be described in detail below with reference to examples, but the present embodiment is not limited to these examples.
[0106] <Materials used> The materials used in the examples and comparative examples are listed below.
[0107] [Multifunctional urethane (meth)acrylate (A)] A-1: Bifunctional urethane acrylate; "KAYARAD UX-6101" (manufactured by Nippon Kayaku Co., Ltd., weight average molecular weight (measured value): 6.7 × 103 ) A-2: Bifunctional urethane acrylate; "KAYARAD UX-8101" (manufactured by Nippon Kayaku Co., Ltd., weight average molecular weight (measured value): 3.3 × 10 3 ) A-3: Bifunctional urethane acrylate; "CN9001NS" (Arkema, weight average molecular weight (measured value): 5.4 × 10 3 )
[0108] [Hydrophilic monofunctional radical polymerizable compound (B)] B-1: Acryloylmorpholine; "ACMO" (KJ Chemicals) B-2: N,N-diethylacrylamide; "DEAA" (KJ Chemicals) B-3: N-vinylcaprolactam B-4: 2-Hydroxyethyl methacrylate B-5: Diacetone acrylamide; "DAAM" (KJ Chemicals)
[0109] [Hydrophobic monofunctional radical polymerizable compound (C)] C-1: Isobornyl acrylate C-2: N-phenylmaleimide; "imilex-P" (manufactured by Nippon Shokubai Co., Ltd.) C-3: N-cyclohexylmaleimide; "imilex-C" (manufactured by Nippon Shokubai Co., Ltd.)
[0110] [Rubber particles (D)] Acetone dispersions of rubber particles D-1 and D-2 were prepared by the following method.
[0111] <Preparation of acetone dispersion of rubber particles D-1> In a 1L glass container, 185 parts by mass of polybutadiene latex (Nipol LX111A2: manufactured by Nippon Zeon Co., Ltd.) (corresponding to 100 parts by mass of polybutadiene rubber particles) and 315 parts by mass of deionized water were charged and stirred at 60°C while nitrogen substitution was performed. Furthermore, 0.005 parts by mass of disodium ethylenediaminetetraacetate (EDTA), 0.001 parts by mass of ferrous sulfate heptahydrate, and 0.2 parts by mass of sodium formaldehyde sulfoxylate were added. Then, a mixture of 35 parts by mass of a radical polymerizable compound to form a shell (17.5 parts by mass of methyl methacrylate (MMA), 17.5 parts by mass of isobornyl methacrylate (IBMA)) and 0.1 parts by mass of cumene hydroperoxide was continuously added over 2 hours. As a result, the radical polymerizable compound was graft polymerized onto the surface of the polybutadiene rubber particles. After the addition of the shell-forming material was completed, the mixture was stirred for an additional 2 hours to terminate the reaction, thereby obtaining an aqueous dispersion of core-shell type rubber particles D-1 having a polybutadiene rubber core and a copolymer of MMA and IBMA as the shell.
[0112] The aqueous dispersion of the core-shell type rubber particles obtained by the above procedure was poured into 450 parts by mass of acetone and mixed uniformly. The mixture was replaced with acetone using a centrifuge to obtain an acetone dispersion of the core-shell type rubber particles D-1. The average particle size of the core-shell type rubber particles D-1 measured using a dynamic light scattering method was 0.25 μm.
[0113] <Preparation of acetone dispersion of rubber particles D-2> 20 parts by mass of rubber particles D-2 (Kane Ace M-511 (Kaneka Corporation)) and 80 parts by mass of acetone were mixed and dispersed to primary particles using an ultrasonic homogenizer to obtain an acetone dispersion of core-shell type rubber particles D-2. The average particle size of the core-shell type rubber particles D-2 measured using a dynamic light scattering method was 0.23 μm.
[0114] [Radical polymerization initiator (E)] E-1: Photoradical generator; "Irgacure 819" (BASF)
[0115] [Other components (multifunctional radical polymerizable compounds) (F)] F-1: Polycarbonate diol diacrylate "UM-90(1 / 3)DM" (molecular weight: approx. 900, radical polymerizable functional group equivalent: approx. 450g / eq, manufactured by Ube Industries, Ltd.) F-2: Ethoxylated isocyanuric acid triacrylate "A-9300" (molecular weight: 423, radical polymerizable functional group equivalent: 141 g / eq, manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0116] <Production of Curable Resin Composition> The materials were mixed uniformly in the compounding ratios shown in Table 1. An acetone dispersion of rubber particles D-1 or D-2 was mixed into this mixture, and the acetone, which is a volatile component, was removed to obtain curable resin compositions according to Examples 1 to 13 and Comparative Examples 1 to 6.
[0117] <Preparation of test specimen> A cured product was produced from the prepared curable resin composition by the following method. First, a mold with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm was sandwiched between two pieces of quartz glass, and the curable resin composition was poured into the mold. The poured curable resin composition was irradiated with 5 mW / cm2 UV light by an ultraviolet irradiator (manufactured by HOYA CANDEO OPTRONICS, product name "LIGHT SOURCE EXECURE3000"). 2 The mold was irradiated with ultraviolet light from both sides for 180 seconds each, twice. The cured product was placed in a 70°C oven and heat-treated for 2 hours to obtain a test piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm.
[0118] <Evaluation> [Weight average molecular weight] Two Shodex GPC LF-804 columns (Showa Denko, molecular weight exclusion limit: 2×106, separation range: 300-2×106) were arranged in series in a gel permeation chromatography (GPC) apparatus (Tosoh, HLC-8220GPC), and measurements were performed at 40°C using THF as a developing solvent with an RI (Refractive Index) detector. The weight average molecular weight obtained is a standard polystyrene equivalent value.
[0119] [Average particle size of rubber particles] Using a particle size distribution analyzer (Malvern, Zetasizer Nano ZS), about 1 ml of a dilute acetone dispersion of rubber particles (D-1) was placed in a glass cell and the arithmetic (number) average particle size was measured at 25°C.
[0120] [Glass transition temperature (Tg) of polymers of monofunctional radical polymerizable compounds] The Tg of the polymer of the monofunctional radical polymerizable compound was calculated using the FOX formula for the polymer of a commonly known monofunctional radical polymerizable compound, and was measured with a viscoelasticity measuring device (Physica MCR302, manufactured by Anton Paar) for the others. The Tg of the polymer of the monofunctional radical polymerizable compound is shown in Table 1 as ◯ when it is 85°C or higher, and × when it is less than 85°C.
[0121] [Viscosity of Curable Resin Composition] The viscosity of the curable resin composition was measured by a rotational rheometer method, specifically, using a viscoelasticity measuring device (Physica MCR302, manufactured by Anton Paar) as follows.
[0122] Approximately 0.5 mL of sample is filled into the measurement device equipped with a cone-plate type measurement jig (CP25-2, manufactured by Anton Paar; 25 mm diameter, 2°) and adjusted to 25°C. -1 The viscosity was measured at a data interval of 6 seconds under a constant shear rate condition of 120 seconds. The viscosity was evaluated according to the following criteria. A (very good): Viscosity less than 2.0 Pa s B (Good): Viscosity is 2.0 Pa s or more and less than 5.0 Pa s C (bad): Viscosity is 5.0 Pa s or more
[0123] [Deflection temperature under load] The test pieces were subjected to a bending stress of 1.80 MPa using a deflection temperature under load tester (manufactured by Toyo Seiki Seisakusho, product name "No. 533 HDT Testing Machine 3M-2") in accordance with JIS K 7191-2, and the temperature was raised from room temperature at a rate of 2°C per minute. The temperature at which the deflection of the test piece reached 0.34 mm was taken as the deflection temperature under load and was used as an index of heat resistance. The results are shown in Table 1. Heat resistance was evaluated according to the following criteria. A (very good): Deflection temperature under load is 80°C or higher B (Good): Deflection temperature under load is 60℃ or higher and less than 80℃ C (bad): Deflection temperature under load is less than 60°C
[0124] [Charpy impact strength] According to JIS K 7111, a notch of 2 mm depth and 45° was made in the center of the test piece using a notch forming machine (manufactured by Toyo Seiki Seisakusho, product name "Notching Tool A-4"). Using an impact tester (manufactured by Toyo Seiki Seisakusho, product name "IMPACT TESTER IT"), the test piece was broken with an energy of 2 J from the back of the notch. The energy required for breaking was calculated from the angle at which the hammer, which had been swung up to 150°, swung up after the test piece was broken, and this was taken as the Charpy impact strength, which was used as an index of impact resistance. The results are shown in Table 1. Impact resistance was evaluated according to the following criteria. A (very good): Charpy impact strength is 12 kJ / m 2 End B (Good): Charpy impact strength is 8 kJ / m 2 More than 12kJ / m 2 Less than C (poor): Charpy impact strength is 8 kJ / m 2 less than
[0125] [Water absorption rate] The test piece was dried at 50°C for 24 hours and weighed, and the value was defined as M1 (g). The test piece was immersed in 300 ml or more of water and left at room temperature for 24 hours, after which the surface moisture was wiped off and the test piece was weighed, and the value was defined as M2 (g). The water absorption rate was calculated using the following formula. Water absorption rate [%]=(M2-M1) / M1×100
[0126] The water absorption rate was evaluated according to the following criteria. A (very good): Water absorption rate is less than 2.0% B (Good): Water absorption rate is 2.0% or more and less than 10%. C (poor): Water absorption rate is 10% or more
[0127] [Table 1]
[0128] In Table 1, a blank cell means that the material was not included in the composition.
[0129] As shown in Table 1, the curable resin compositions prepared in Examples 1 to 13 had viscosities within a suitable range for use as a modeling material in stereolithography. In addition, the obtained cured products had excellent impact resistance and heat resistance, low water absorption, and excellent water resistance.
[0130] On the other hand, the cured product according to Comparative Example 1 obtained from a curable resin composition not containing hydrophobic monofunctional radical polymerizable (C) had a high water absorption rate, which was at a level that caused practical problems. The curable resin composition according to Comparative Example 2 not containing hydrophilic monofunctional radical polymerizable (B) had an extremely high viscosity, which was at a level that made it difficult to mold using a stereolithography method. The cured product according to Comparative Example 3 obtained from a curable resin composition containing a small amount of rubber particles (D) of 5 parts by mass did not have a sufficient improvement in impact resistance. In addition, the cured product according to Comparative Example 4 obtained from a curable resin composition containing a polymer of a monofunctional radical polymerizable compound with a low glass transition temperature of less than 85°C did not have sufficient heat resistance. Furthermore, the cured product according to Comparative Example 5 obtained from a curable resin composition containing a large amount of a polyfunctional radical polymerizable compound with a radical polymerizable functional group equivalent of less than 300 g / eq of 25 parts by mass did not have a sufficient improvement in impact resistance. Similarly, the cured product of Comparative Example 6, which was obtained from a curable resin composition containing a high content of 50 parts by mass of a polyfunctional radically polymerizable compound having a radically polymerizable functional group equivalent of 300 g / eq or more, did not have sufficient heat resistance.
[0131] From the above results, it was confirmed that the present invention provides a curable resin composition having a viscosity suitable for stereolithography, and that by curing the composition, a cured product having good impact resistance, low water absorption, and heat resistance can be obtained.
Claims
1. A curable resin composition comprising: The curable resin composition contains a polyfunctional urethane (meth)acrylate (A), a hydrophilic monofunctional radical polymerizable compound (B), a hydrophobic monofunctional radical polymerizable compound (C), rubber particles (D), and a radical polymerization initiator (E); The hydrophilic monofunctional radically polymerizable compound (B) contains at least one of an acrylamide compound and an N-vinyl compound, The content of the rubber particles (D) is 8 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the radical polymerizable compound, A curable resin composition, characterized in that the weight average molecular weight of the polyfunctional urethane (meth)acrylate (A) is 1,000 or more and 60,000 or less.
2. A curable resin composition comprising: The curable resin composition contains a polyfunctional urethane (meth)acrylate (A), a hydrophilic monofunctional radical polymerizable compound (B), a hydrophobic monofunctional radical polymerizable compound (C), rubber particles (D), and a radical polymerization initiator (E); The hydrophilic monofunctional radically polymerizable compound (B) contains at least one of an acrylamide compound and an N-vinyl compound, The content of the rubber particles (D) is 8 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the radical polymerizable compound, The curable resin composition, wherein the polyfunctional urethane (meth)acrylate (A) has a radical polymerizable functional group equivalent of 400 g / eq or more.
3. The curable resin composition according to claim 2 , wherein the polyfunctional urethane (meth)acrylate (A) has a weight average molecular weight of 1,000 or more and 60,000 or less.
4. The curable resin composition according to claim 1 , wherein a content of the hydrophilic monofunctional radically polymerizable compound (B) is 65 parts by mass or less per 100 parts by mass in total of the hydrophilic monofunctional radically polymerizable compound (B) and the radically polymerizable compound.
5. The curable resin composition according to any one of claims 1 to 4, wherein the content of the hydrophilic monofunctional radically polymerizable compound (b-1) having a solubility in water of 20 [g / 100 g] or more in the hydrophilic monofunctional radically polymerizable compound (B) is 55 parts by mass or less per 100 parts by mass of the total of the hydrophilic monofunctional radically polymerizable compound and the radically polymerizable compound.
6. The curable resin composition according to any one of claims 1 to 5, wherein a content of the hydrophobic monofunctional radically polymerizable compound (c-1) having an alicyclic hydrocarbon group in the hydrophobic monofunctional radically polymerizable compound (C) is less than 60 parts by mass relative to a total of 100 parts by mass of the radically polymerizable compounds in the curable resin composition.
7. 7. The curable resin composition according to claim 1, wherein the content of the polyfunctional radically polymerizable compound having a radically polymerizable functional group equivalent of less than 300 g / eq is 20 parts by mass or less relative to a total of 100 parts by mass of the radically polymerizable compounds in the curable resin composition.
8. The curable resin composition according to any one of claims 1 to 7, wherein a copolymer of the hydrophilic monofunctional radical polymerizable compound (B) and the hydrophobic monofunctional radical polymerizable compound (C) has a glass transition temperature of 85°C or higher.
9. The curable resin composition according to claim 1 , wherein the content of the rubber particles (D) is 10 parts by mass or more and 40 parts by mass or less based on 100 parts by mass of the radical polymerizable compound.
10. The curable resin composition according to claim 1 , wherein the viscosity of the curable resin composition at 25° C. is less than 5.0 Pa·s.
11. A cured product of the curable resin composition according to any one of claims 1 to 10.
12. The cured product according to claim 11, wherein the cured product has a deflection temperature under load of 60°C or higher.
13. The Charpy impact strength of the cured product is 8 kJ / m 2 The cured product according to claim 11 or 12.
Citation Information
Patent Citations
Curable resin composition, adhesive composition, cured product, composite and adhesion process
JP2000351819A
Resin composition for optical stereolithographic shaping and stereolithographic shaped product
JP2004051665A
Active energy ray-curing type adhesive composition
JP2013112715A
Photocurable resin composition
JP2014201688A
Energy ray-curable resin composition using unsaturated carbonyl modified conjugated diene-based hydrogenated polymer
JP2015007191A